Full- Versus Part-Day Kindergarten for Children With Disabilities: Effects on Executive Function Skills. Issue 2 (17th February 2018) - Gottfried, Michael A.; Little, Michael H.
ABSTRACT: Responding to a robust body of literature suggesting that children's early educational experiences are critical, policymakers have implemented and expanded the provision of full-day kindergarten (FDK) in recent decades. Most studies have focused on the effectiveness of FDK on child academic assessments or test scores, but none have examined FDK and the link to executive function skills. Moreover, little work exists on the effectiveness of FDK for children with disabilities. The purpose of this study is to build on these incipient lines of research by estimating the effect of FDK on the executive function skills of children with disabilities. Drawing on data from a nationally representative sample of children with disabilities ( n = 2, 120) from the Early Childhood Longitudinal Study–Kindergarten Class of 2010–2011, we find significant positive effects of FDK on working memory ( SD = 0.14) and cognitive flexibility ( SD = 0.14) for children with disabilities in kindergarten. Despite significant immediate effects, the benefits of FDK rapidly fade by the end of 2nd grade. Practice or Policy : Policy implications and directions for future research are addressed.